ACCOUNTABILITY FOR CORRUPTION IN THE CRIME OF MONEY LAUNDERING IN THE PRINCIPLES OF CRIMINAL LAW IN INDONESIA - Karolus Agung Dery Rianto; Rahmayanti (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The purpose of this writing is to find out the forms of money laundering carried out by corporate actors, to find out the form of responsibility of a company in the crime of money laundering, to examine the forms of responsibility for corporate criminal acts in the regulations existing in legislation and to examine non-criminal liability. corporations in money laundering criminal cases. This writing is descriptive in order to get a picture of the existing problems, which are then analyzed deductively. There are three types of criminal money laundering by corporations, namely placing, layering and merging. Corporate subjects will receive criminal penalties according to their actions. As stated in article 6 of Law No. 8 of 2010, money laundering as referred to in articles 3, 4 and 5 is carried out by corporations so that penalties will be imposed on corporate control personnel. If personnel are unable to pay, they will be replaced by confiscation of the corporation and the company's controlling personnel. And if that is not enough, prison can be replaced by a company control fine.